RAKYAT MEMPERKUAT KENDALINYA TERHADAP NEGARA - Merphin Panjaitan (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractThe people’s goal to established the a state is to get better life, justice, secure and welfare.But in the New Order, injustice was almost happened in all fields of lives, which was thenfall into an economic crisis leaving broad poverty, unemployment, backward education andcorruption. Those New Order’s diseases are still continue up till now, although reformationhas been continued for more than 10 years. In reality the state’s power is not always used toserve its people. Thus, people has to tightened its control toward state, since when onceloose its control, state’s power will be misused only for the interest of the ruler and at thesame time forget the people who actually is the owner of the state. The state is owned bypeople for the common good and that kind of state is named democratic state that its processof execution must be under people’s control. For that purpose it needed a kind of politicalinteraction between state-society which is peaceful, secure, fairness and having trust to eachother. That interaction needs appropriate condition, among other things are limited statepower, power division based on check and balance principle, general election, effectivepolitical participation, regional autonomy and reformation of the behavior of society andstate.Keywords: State power, People’s control, Democratic state,Behavior reform of state and society